Imperfect Mobility - Zhengyu Cai (Global Labor Organization (GLO), 2020)
This study investigates why the strong form of the spatial equilibrium is weakly supported in the literature. Using a discrete choice model, it shows that the strong form of the spatial equilibrium is rarely observed because workers are imperfectly mobile from the perspective of researchers. Incorporating the discrete choice model, a Markov chain is used to model the spatial dynamics of the population distribution. For a given location choice set, the population distribution is shown to converge to a unique spatial steady state. Microdata from the American Community Survey show that the model assumption is reasonable and support the model predictions.
Keywords: J61; R10; C25; C15; C44; 330; imperfect mobility; heterogeneity; spatial steady state; discrete choice model; Markov chain analysis